A study of outcomes in patients undergoing nerve preserving surgery in colorectal cancers - Chandrakar, Sandeep; Ratre, Rajendra; Gupta, Ashutosh; Agrawal, Harsh M.; R., Avinash (International Surgery Journal, 2022)
Background: Colorectal cancers are third most commonly diagnosed cancer globally. Its management consist mainly of surgical intervention to achieve an oncologic cure but also to preserve function. Introduction of nerve-preserving TME technique, spares the nerve and plexus pivotal for urinary and sexual function. The study assessed the urinary and sexual function after nerve sparing colorectal surgery. Aims and objective were to check functional outcomes after nerve preservation in patient undergoing colorectal cancer surgery, in terms of urinary and sexual function. Methods: A prospective observational study conducted from January 2019 to July 2020, in the department of surgery and oncosurgery, Dr. BRAM Hospital, Raipur, Chhattisgarh. Results: According to IPSS score, post-operatively, 57.5% showed fair urinary function, 22.5% showed good urinary function and 20% showed poor urinary function at 1 month. At 3 months, 80% showed good urinary function, 15% showed fair urinary function and 5% showed poor urinary function. According to IIEF score in males, post-operatively, at 1 month, 52% had a fair score, 40% had a poor score and 8% had a good score. At 3 months, 68% had a good score, 24% had a fair score and 8% had a poor score. According to FSFI score in females, post-operatively, at 1 month, 40% had a good score, 26.6% had fair score and 33.33% had a poor score. At 3 months, 66.67% had a good score, 13.33% had a fair score and 20% had a poor score. Conclusions: Nerve preserving surgery in colorectal cancer significantly preserves urinary and sexual function.